Strategies targeting endoplasmic reticulum stress to improve Parkinson’s disease - Wang, Danni; Qu, Shuhui; Zhang, Zaijun; Tan, Liang; Chen, Xiuping; Zhong, Hai-Jing; Chong, Cheong-Meng (Frontiers in Pharmacology, 2023)
Parkinson's disease (PD) is a common neurodegenerative disorder with motor symptoms, which is caused by the progressive death of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc). Accumulating evidence shows that endoplasmic reticulum (ER) stress occurring in the SNpc DA neurons is an early event in the development of PD. ER stress triggers the activation of unfolded protein response (UPR) to reduce stress and restore ER function. However, excessive and continuous ER stress and UPR exacerbatesexacerbate the risk of DA neuron death through crosstalk with other PD events. Thus, ER stress is considered a promising therapeutic target for the treatment of PD. Various strategies targeting ER stress through the modulation of UPR signaling, the increase of ER's protein folding ability, and the enhancement of protein degradation are developed to alleviate neuronal death in PD models. In this review, we summarize the pathological role of ER stress in PD and update the strategies targeting ER stress to improve ER protein homeostasis and PD-related events.